2014
DOI: 10.1103/physrevb.90.245412
|View full text |Cite
|
Sign up to set email alerts
|

Quantum sticking of atoms on membranes

Abstract: A continuum model for low-energy physisorption on a membrane under tension is proposed and studied with variational mean-field theory. A discontinuous change in the energy-dependent sticking coefficient is predicted under certain conditions. This singularity is a result of the bosonic orthogonality catastrophe of the vibrational states of the membrane. The energy-dependent sticking coefficient is predicted to have exponential scaling in 1/E above the singularity. The application of this model to the quantum st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…In contrast, in the case of T = 0, the total adsorption rate remains exponentially suppressed as → 0. This exponential suppression of the total adsorption rate is consistent with previous results using a variational mean-field method that show the suppression of adsorption for T = 0 for sufficiently weak atom-phonon coupling strength [4]. Finally, the system studied here provides a mechanical realization for a recent reinterpretation of the infrared problem in QED where "non-trivial scattering" [11] results in vacuum transitions that render matrix elements IR-finite.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, in the case of T = 0, the total adsorption rate remains exponentially suppressed as → 0. This exponential suppression of the total adsorption rate is consistent with previous results using a variational mean-field method that show the suppression of adsorption for T = 0 for sufficiently weak atom-phonon coupling strength [4]. Finally, the system studied here provides a mechanical realization for a recent reinterpretation of the infrared problem in QED where "non-trivial scattering" [11] results in vacuum transitions that render matrix elements IR-finite.…”
Section: Discussionsupporting
confidence: 90%
“…It will be shown that this lack of adsorption is a result of a phonon orthogonality catastrophe that suppresses the adsorption transition. This finding supports a result that was obtained previously by variational means [4].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…We consider micromembranes whose size ranges from 100 nm to 10 µm. These values have been previously used to model [3][4][5] ultracold atomic hydrogen impinging at normal incidence on a suspended, circular sample of graphene.…”
Section: Adsorption Of Atomic Hydrogen On Graphenementioning
confidence: 99%
“…It is important that we point out that within the simple model of IBM implemented for graphene physisorption, our work 1 has revealed that the zero adsorption rate predicted by Ref. [5,4] is only possible if one considers (i) contribution to adsorption rate from the long time regime, where the effects of Franck-Condon factor sets in and (ii) neglects the effects of thermal phonon emission. Points (i) and (ii) are indeed the regime of study in Ref.…”
mentioning
confidence: 90%